Pengaruh Pengetahuan dan Sikap Kerja Terhadap Kinerja Pegawai pada Dinas Peternakan Kabupaten Bima - Muhammad Fadil; Kartin Aprianti (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine the influence of knowledge and work attitudes on employee performance at the Bima Regency Animal Husbandry Service. The sample in this study was 47 respondents with ASN status. Data collection techniques use observation, questionnaires and literature study. The data analysis technique uses multiple linear regression. The research results show that knowledge has no significant effect on employee performance, but work attitude has a significant effect on employee performance. Together, knowledge and work attitudes have a significant influence on the performance of employees at the Bima Regency livestock service.